Strategi Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Sopan Santun pada Siswa Kelas 2 SDN 003 Bontang Barat Tahun Pelajaran 2024/2025 - Hasni, Hasni; Murni, Murni (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This article discusses the strategies employed by Islamic Education (PAI) teachers to instill the values of politeness in second-grade students at SDN 003 Bontang Barat. The study is motivated by the importance of shaping character from an early age, especially as politeness is increasingly diminishing in students’ social interactions. The aim of this research is to describe the strategies used by PAI teachers in cultivating polite behavior among second-grade students at SDN 003 Bontang Barat. The findings indicate that the strategies include: (1) being a role model in polite behavior, (2) habituating greetings, prayers, and polite expressions in daily activities, (3) using storytelling and exemplary figures, (4) giving motivation and direct advice to students, and (5) utilizing the school environment as a medium for habituation. The study also found that the strategies implemented by PAI teachers are effective in instilling politeness values, particularly when supported by the school environment and parental involvement. The novelty of this research lies in its focus on lower-grade students (second grade) and the application of concrete, comprehensive, and contextually appropriate strategies.